Real-time ultrasound assessment of sternal stability in adhesive-enhanced sternal closure. Issue 3 (2015) - El-Ansary, Doa; Balachandran, Sulakshana; Royse, Alistair; King-Shier, Kathryn; Bryant, Adam; Denehy, Linda
No abstract available